Old Methods in The Cyberspace? (CYBER-HUMINT, OSINT, SOCMINT, Social Engineering) (Academic Journal of Internal Affairs, 2021)
This study examines the emergence and category boundaries of the traditional HUMINT in the cyberspace, which is a dynamically developing field nowadays. The issue of CYBER-HUMINT has appeared in the last ten years, and its conceptual category hasn’t been still fixed with exact boundaries. Its international literature can be regarded as relatively scarce, similar to the issue of the method of gathering information using social networking sites (SOCMINT). However, there is an abundance of literature on open source information gathering (OSINT) and the phenomenon of social engineering (SE), whose methodological boundaries often overlap with HUMINT in the cyberspace. The aim of the publication is to review the increasingly intertwined areas of information gathering, making an attempt to prepare a system of criteria that promotes demarcation.Arrived: 22 August 2020Accepted: 20 Sept 2020
Keywords: national security; HUMINT; CYBER-HUMINT; cyberspace